Reflections from the Margins. Engaging with Mobile Peoples: the inevitability of the road taken - Chatty, Dawn (Antropologia Pubblica, 2024)
Careers in anthropology are often profoundly influenced by early life experience. Ivory tower academia and practical solution-focused anthropological engagement are not necessarily exclusionary, but the attraction of one over the other is often grounded in the early life course and chosen education path which followed. There was something almost inevitable about my journey into academia and into applied / development anthropology. And like so many other anthropologists, I had an early life experience of other cultures, societies, and countries. Such experiences inevitably created a rich sense of what it is to be the “other”, the significant subject of anthropological theorizing. Along with such othering came a profound sense of shock at the social discrimination which “others” faced. It was this recognition of differences in attitudes and behaviour in other societies and social groups in early life that very much shaped the way I understood the anthropological “other”. It also impacted significantly on how I understood and addressed, in anthropological terms, the potentially different solutions to the problems of living together in groups often adjacent to other groups in unequal, power-imbalanced relationships.